Buprenorphine treatment retention and comorbidities among patients with opioid use disorder in a primary care setting. Issue 3 (6th April 2022) - Sweeney, Mary M.; Prichett, Laura; Fingerhood, Michael I.; Antoine, Denis; Umbricht, Annie; Dunn, Kelly E.; Buresh, Megan E.
Abstract: Background and Objectives: More information is needed about comorbidities among patients receiving buprenorphine maintenance treatment and their relationship with retention. Methods: Retrospective electronic health record data over a 5‐year period from primary care patients receiving buprenorphine for the treatment of opioid use disorder were examined ( N = 899). The present analysis determined the prevalence of comorbidities and examined associations with treatment retention as defined by cumulative duration of buprenorphine prescription. Results: Tobacco use and comorbidities including hypertension were prevalent but did not predict retention according to survival analyses controlling for demographic characteristics. Retention was poorer among patients testing positive for cocaine (HR = 1.38, 95% CI: 1.09–1.74, p = .007) and patients with hepatitis C virus (HR = 1.17, 95% CI: 1.01–1.37, p = .04). Conclusion and Scientific Significance: This study provides new knowledge of previously unexamined associations between comorbidities (e.g., hypertension) and buprenorphine treatment retention. The robust association between cocaine use and poorer buprenorphine retention serves to resolve prior conflicting data in the literature.